2018
DOI: 10.1093/sleep/zsy056
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiological basis of the discrepancy between objective and subjective sleep during the sleep onset period: an EEG-fMRI study

Abstract: Subjective perception of sleep is not necessarily consistent with electroencephalography (EEG) indications of sleep. The mismatch between subjective reports and objective measures is often referred to as "sleep state misperception." Previous studies evince that this mismatch is found in both patients with insomnia and in normal sleepers, but the neurophysiological mechanism remains unclear. The aim of the study is to explore the neurophysiological basis of this mechanism, from the perspective of both EEG power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…We assume that the transitions of sleep cycle affect sleep perception, and the judgment of sleep cycles is accomplished through EEG activity. Previous studies have found that there is a connection between sleep perception and EEG, which reflects that the amplitude of low-frequency waves in the prefrontal cortex of negative sleep perception patients is higher than that of the normal control group, and the activity of alpha wave and gamma wave is strengthened (18). In 1982, MG Terzano et al proposed an alternating pattern of EEG circulation during sleep, which is a periodic EEG change in NREM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that the transitions of sleep cycle affect sleep perception, and the judgment of sleep cycles is accomplished through EEG activity. Previous studies have found that there is a connection between sleep perception and EEG, which reflects that the amplitude of low-frequency waves in the prefrontal cortex of negative sleep perception patients is higher than that of the normal control group, and the activity of alpha wave and gamma wave is strengthened (18). In 1982, MG Terzano et al proposed an alternating pattern of EEG circulation during sleep, which is a periodic EEG change in NREM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the two is often referred to as "sleep state misperception" [36]. Such misperception commonly exists among healthy adults [40] but could be more pronounced in pregnant women [76] and in clinical populations with Alzheimer disease, depression and sleep problems [38,44,62,71,87]. As we will show later in the findings, the discrepancy between objective measurements and subjective sleep experience adds an extra layer of complexity for participants to assess the credibility of sleep data.…”
Section: Related Work 21 Fundamentals Of Human Sleepmentioning
confidence: 89%
“…Regardless of measuring the same phenomenon, subjective sleep quality and objective sleep quality are only moderately correlated [40,90]. The discrepancy between the two is often referred to as "sleep state misperception" [36].…”
Section: Related Work 21 Fundamentals Of Human Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the positive effect of slow wave sleep on memory retention is also attenuated in older individuals (Cherdieu, Reynaud, Uhlrich, Versace, & Mazza, ), supporting the hypothesis of a change in the function of slow waves. Increased alpha power in sleep, on the other hand, has previously been identified as a marker of poor sleep quality/sleep state misperception in younger adults (Hsiao et al., ). It would be interesting for further research to investigate whether our finding that this relationship seems to be absent in older adults can be replicated.…”
Section: Discussionmentioning
confidence: 99%